In vitro and in vivo studies of the Interferon-alpha action on distinct Orthobunyavirus - Livonesi, Marcia Cristina; Moro de Sousa, Ricardo Luiz; Badra, Soraya Jabur; Moraes Figueiredo, Luiz Tadeu (Elsevier B.V., 2007)
Oropouche, Caraparu, Guama, Guaroa and Tacaiuma viruses (Orthobunyavirus genus) cause human febrile illnesses and/or encephalitis. To achieve a therapeutical agent to prevent and/or treat these diseases we evaluated the antiviral action of Interferon-alpha (IFN-alpha) on these orthobunyaviruses. In vitro results showed that all the studied orthobunyaviruses are susceptible to antiviral action of IFN-alpha, but this susceptibility is limited and dependent on both concentration of drug and treatment period. In vivo results demonstrated that IFN-alpha present antiviral action on Oropouche and Guaroa viruses when used as a prophylactic treatment. Moreover, a treatment initiated 3 It after infection prevented the death of Guaroa virus infected-mice. Additionally, mortality of mice was related to the migration and replication of viruses in their brains. Our results suggest that IFN-alpha could be potentially useful in the prevention of diseases caused by Oropouche virus and in the prevention and/or treatment of diseases caused by Guaroa virus. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: interferon-alpha; Orthobunyavirus; Bunyaviridae; plaque assay; suckling mice